An extremely rare case of classic complete caudal duplication: Dipygus - Yasen Fayez Al Alayet; Ram Samujh; Toijam Soni Lyngdoh; Khizer Mansoor; Fawaz Al Kasim; Abdulaziz A Al-Mustafa (Wolters Kluwer Medknow Publications, 2014)
Dipygus is a complete caudal duplication deformity in its severest form. The structures derived from the embryonic cloaca and notochords are duplicated to various extent. We report a male baby who presented to us with complete somatic and visceral duplication below the umbilical level associated with gastroschisis and imperforated anus. Staged surgical corrections were suggested and three out of the four stages were performed successfully.